Addition of Zygomatic Arch resection in Decompressive Craniectomy - Arvind G. Martin; Johari Yap Abdullah; Azlan Jaafar; Abdul Rahman Izaini Ghani; Zainul A. Rajion; Jafri Malin Abdullah (Elsevier BV, 2024)
Journal of Clinical Neuroscience Volume 22 Issue 4 Page (735–739)